PENGARUH KEPEMIMPINAN MANAJERIAL, BUDAYA PERUSAHAAN, RENCANA BISNIS TERHADAP DAYA SAING PERUSAHAAN PADA PT ADITYA MANDIRI SEJAHTERA - Rosa Rachmat Septian (POLITEKNIK LP3I JAKARTA, 2018)
ABSTRACTThe objective of this research is to systematically test the Influence of Managerial Leadership, Corporate Culture, Business Plan to Competitiveness of PT. Aditya Mandiri Sejahtera. Samples used are employees of PT. Aditya Mandiri Sejahtera with the number of respondents as many as 100 people. The analysis used is multiple linear regression. This study examines four variables: Managerial Leadership (X1), Corporate Culture (X2), Business Plan (X3) as the independent variable and Competitiveness Company (Y) as the dependent variable. Partial test shows that managerial leadership influence 3,498 (positive and significant) to competitiveness of company. The corporate culture of 1,899 has no effect on the competitiveness of the company. Furthermore, the business plan has a significant effect of 2,176 on competitiveness. By performing multiple linear regression analysis using SPSS, it can be seen that the correlation coefficient (R) = 0.574 meaning that the relationship between the variables of the performance is very strong and positive. Keywords: Managerial Leadership, Corporate Culture, Business Plan, Corporate Competitiveness, 50 and Multiple Linear Regression